Evaluation and Comparison of the Efficiency of Transcription Terminators in Different Cyanobacterial Species - Gale, Grant A. R.; Wang, Baojun; McCormick, Alistair J. (Frontiers in Microbiology, 2021)
Cyanobacteria utilise sunlight to convert carbon dioxide into a wide variety of secondary metabolites and show great potential for green biotechnology applications. Although cyanobacterial synthetic biology is less mature than for other heterotrophic model organisms, there are now a range of molecular tools available to modulate and control gene expression. One area of gene regulation that still lags behind other model organisms is the modulation of gene transcription, particularly transcription termination. A vast number of intrinsic transcription terminators are now available in heterotrophs, but only a small number have been investigated in cyanobacteria. As artificial gene expression systems become larger and more complex, with short stretches of DNA harbouring strong promoters and multiple gene expression cassettes, the need to stop transcription efficiently and insulate downstream regions from unwanted interference is becoming more important. In this study, we adapted a dual reporter tool for use with the CyanoGate MoClo Assembly system that can quantify and compare the efficiency of terminator sequences within and between different species. We characterised 34 intrinsic terminators in Escherichia coli, Synechocystis sp. PCC 6803 and Synechococcus elongatus UTEX 2973 and observed significant differences in termination efficiencies. However, we also identified five terminators with termination efficiencies of >96% in all three species, indicating that some terminators can behave consistently in both heterotrophic species and cyanobacteria.